2014
DOI: 10.1155/2014/231651
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-Induced Thyrotoxic Thyroiditis: A Diagnostic and Therapeutic Challenge

Abstract: Amiodarone is an iodine-based, potent antiarrhythmic drug bearing a structural resemblance to thyroxine (T4). It is known to produce thyroid abnormalities ranging from abnormal thyroid function testing to overt hypothyroidism or hyperthyroidism. These adverse effects may occur in patients with or without preexisting thyroid disease. Amiodarone-induced thyrotoxicosis (AIT) is a clinically recognized condition commonly due to iodine-induced excessive synthesis of thyroid, also known as type 1 AIT. In rare instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
3
0
5
Order By: Relevance
“…[3,6,9] In severely ill patients, treating both AIT1 and AIT2 with anti-thyroid drugs and glucocorticoids with or without perchlorate reduces thyroid inflammation and also reduces the peripheral conversion of T4 to T3. [5,9,10] …”
Section: Discussionmentioning
confidence: 99%
“…[3,6,9] In severely ill patients, treating both AIT1 and AIT2 with anti-thyroid drugs and glucocorticoids with or without perchlorate reduces thyroid inflammation and also reduces the peripheral conversion of T4 to T3. [5,9,10] …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that thyroid surgery is a valid therapeutic option in a small subgroup (7% out of 394 patients) of AIT patients with severe left ventricular dysfunction (20). In general, subtotal or total thyroidectomy should be considered only in patients with progressive AIT when patients are resistant to a highdose prednisolone and watchful medical management could have negative effects (22,23). In general, subtotal or total thyroidectomy should be considered only in patients with progressive AIT when patients are resistant to a highdose prednisolone and watchful medical management could have negative effects (22,23).…”
Section: Page 7 Of 18mentioning
confidence: 99%
“…Pri tipu 2, ki je redkejši in se pojavlja pri osebah brez predhodnih ščitničnih bolezni, amiodaron sproži destruktivno vnetje ščitnice, kar vodi v sproščanje prej sintetiziranih ščitničnih hormonov v krvni obtok. Možna je tudi kombinacija obeh tipov (4,5). Pojav z amiodaronom povzročene hipertiroze je običaj-no nenaden, pri čemer se tip 1 pogosto pojavi v prvih mesecih uporabe amiodarona, medtem ko je srednji čas pojavljanja tipa 2 okoli 30 mesecev po pričetku zdravljenja (5).…”
Section: Uvodunclassified
“…Možna je tudi kombinacija obeh tipov (4,5). Pojav z amiodaronom povzročene hipertiroze je običaj-no nenaden, pri čemer se tip 1 pogosto pojavi v prvih mesecih uporabe amiodarona, medtem ko je srednji čas pojavljanja tipa 2 okoli 30 mesecev po pričetku zdravljenja (5). Amiodaron preko inhibicije 5'-dejodaze zavira periferno pretvorbo tiroksina (T4) v trijodtironin (T3) ter tako poviša serumsko koncen- tracijo T4, zniža koncentracijo T3 in poviša koncentracijo reverzne oblike T3, ki fiziološko ni aktivna (1,2,5).…”
Section: Uvodunclassified
See 1 more Smart Citation